Plasmonic gold nanoparticles coated TiO2 photoanode for efficiency enhancement in dye-sensitized solar cells (DSSCs) - Shah, Shahan; Abidin, Z. H. Z.; Noor, I. M.; Osman, Z.; Arof, A. K. (Taylor and Francis, 2023)
In this work, gold nanoparticles (NPs) of 100 nm in size were added to the active layer of DSSC. The electrolyte is a gel polymer electrolyte (GPE) containing PEO, PhCh, TPAI, BMII, I2, DMF, EC, TBP, and GuSCN. The DSSCs have been characterized via J–V characteristics, IMVS, and IMPS measurements. On illumination at AM 1.5, the cell with 3 wt. Au NP in the photoanode exhibits an η of 8.56 with Jsc of 19.82 mA cm−2, Voc of 0.72 V and FF of 60. The same cell also exhibited the lowest τtr of 7.32 ms and longest τrec of 115.33 ms.